Mining reflective continuing medical education data for family physician learning needs - Denice Colleen Lewis; Pierre Pluye; Charo Rodriguez; Roland Grad (Journal of Innovation in Health Informatics, 2016)
A mixed methods research (sequential explanatory design) studied the potential of mining the data from the consumers of continuing medical education (CME) programs, for the developers of CME programs. The quantitative data generated by family physicians, through applying the information assessment method to CME content, was presented to key informants from the CME planning community through a qualitative description study.The data were revealed to have many potential applications including supporting the creation of CME content, CME program planning and personal learning portfolios.